2013
DOI: 10.1104/pp.113.215798
|View full text |Cite
|
Sign up to set email alerts
|

CYCLIN H;1 Regulates Drought Stress Responses and Blue Light-Induced Stomatal Opening by Inhibiting Reactive Oxygen Species Accumulation in Arabidopsis      

Abstract: Arabidopsis (Arabidopsis thaliana) CYCLIN-DEPENDENT KINASE Ds (CDKDs) phosphorylate the C-terminal domain of the largest subunit of RNA polymerase II. Arabidopsis CYCLIN H;1 (CYCH;1) interacts with and activates CDKDs; however, the physiological function of CYCH;1 has not been determined. Here, we report that CYCH;1, which is localized to the nucleus, positively regulates blue light-induced stomatal opening. Reduced-function cych;1 RNA interference (cych;1 RNAi ) plants exhibited a drought tolerance phenotype.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 56 publications
1
29
0
Order By: Relevance
“…3b,c). Various stimuli can lead to stomatal closure, but stomatal opening is predominately evoked by means of wavelength-responsive mechanisms 27 . The regulatory mechanism of stomatal opening by blue light has been well studied in a number of C 3 plants 28,29 , but its role is less clear in CAM plants 30 light-induced switch from C 3 to CAM in Clusia minor 31 .…”
mentioning
confidence: 99%
“…3b,c). Various stimuli can lead to stomatal closure, but stomatal opening is predominately evoked by means of wavelength-responsive mechanisms 27 . The regulatory mechanism of stomatal opening by blue light has been well studied in a number of C 3 plants 28,29 , but its role is less clear in CAM plants 30 light-induced switch from C 3 to CAM in Clusia minor 31 .…”
mentioning
confidence: 99%
“…The above mentioned two WRKY family transcription factors might be also involved in PeGs biosynthesis in C. salsa. Interestingly, dehydration related ESTs (CISTH067, CISTH064) were found in the SSH library, which may suggest that the H 2 O 2 treatment was related to dehydration responsive genes expression in C. salsa as observed in other plants (Schmidt et al 2013, Zhou et al 2013. One gibberellin (GA) signalling related gene, gibberellin receptor gid1b-like (CISTH092), was identified in the SSH library implying the connection of GA signalling and H 2 O 2 treatment in C. salsa, which was also reported in barley (Bahin et al 2011).…”
Section: Discussionmentioning
confidence: 87%
“…CYCH;1 induces the expression of redox homeostasis genes, such as LIPOXYGENASE3 (LOX3), LOX4, ARABIDOPSIS GLUTATHIONE PEROXIDASE 7 (ATGPX7), EARLY LIGHT-INDUCIBLE PROTEIN1 (ELIP1), and ELIP2, and increased hydrogen peroxide production in guard cells. The downregulation of CYCH;1 impaired the blue light-induced stomatal opening but did not affect the guard cell development or ABA-mediated stomata closure (Zhou et al 2013 ). This clearly suggested that there exist distinct mechanisms for opening stomata under optimal light condition and for closing under stress condition.…”
Section: Stomata Movementmentioning
confidence: 99%